Analysis of the potential inappropriate use of medications in pediatric outpatients in China - Jing Cui; Lei Zhao; Xianghong Liu; Mengyujie Liu; Lihong Zhong (BMC, 2021)
Abstract Background The appropriate use of medications is essential in children. Yet, detailed information on how drugs are being prescribed and dispensed to pediatric populations is not documented in China. Aim The study objective was to analyze the details of medicine use and categorize the types of inappropriate use of medications on children. Methods A retrospective cross-sectional study was conducted on the prescriptions of pediatric outpatients aged < 18 years from 2019 to 2020 at a major Chinese tertiary academic center. Each age group's demographic and clinical characteristics were collected, and the ratios of inappropriate prescriptions were analyzed. Results The total number of pediatric outpatients was 652,152, and 49.37% (322000) were prescribed medications, in which the most widely used medicines were respiratory, anti-infectives, and Traditional Chinese Medicines (TCMs). The prevalence rate of inappropriate prescriptions reached 20.49%, and in 2019 it was higher (21.71%) than that in 2020 (18.36%). The top three common inappropriate categories were indication-related off-label drug use, improper administration frequency, and overdosing, accounting for 67.93, 17.80 and 11.06% of all inappropriate prescriptions, respectively. The inappropriate prescriptions were more likely seen in patients aged 2-5 years and respiratory medicines. Conclusions The study findings indicate that inappropriate drug use in pediatric outpatients is still common, and great attention needs to be paid. More prospective trials are required to identify the effectiveness, safety, and necessity of off-label drug use of medicines in children.